INVESTIGATION OF GROUNDWATER SOURCES IN BANYOL HAMLET MALANG REGENCY USING THE GEOELECTRICAL RESISTIVITY METHOD TO OVERCOME DROUGHT STRATEGY - Juwono, Alamsyah M.; Susilo, Adi; Hasan, Muhammad Fathur Rouf; Yunika, Nieske Ari; Annabil, Achmad Achdan; Mujtaba, Mochammad Wafa Husain; Haniyyah, Saffanatul (Indonesian Physical Review, 2024)
The drought in Banyol Hamlet, Malang Regency, severely impacts community sustainability. This problem can be overcome if the hamlet has a groundwater source; theoretically, groundwater can be detected using geoelectric resistivity. This research aims to investigate the existence of aquifer layers in Banyol Hamlet, Malang Regency, using the resistivity method Schlumberger configuration. Resistivity data was measured at 5 points with a track stretch of 400 m and a distance between electrodes of 5 m; then, three parallel measurement points were interpolated into a 2D cross-section. Based on the analysis, the presence of the aquifer is considered to be in the breccia tuff layer because the resistivity value is lower than usual in this layer. So, we assume that the tuff breccia rocks can act as an aquifer in the study area. The results of the 2D cross-section show that the shallow aquifer is found at a depth of 10-22 m with a resistivity value of around 30.78 Î©m - 314 Î©m. and a deep aquifer at a depth of 40-125 m with a resistivity value of around 22.34 Î©m - 192 Î©m. So drilling is recommended at measurement points SS-1 and SS-3 in deep aquifers because the thicker the soil layer, the more water infiltration.